2009
DOI: 10.1090/s0002-9939-09-10026-6
|View full text |Cite
|
Sign up to set email alerts
|

Almost commuting unitaries with spectral gap are near commuting unitaries

Abstract: Abstract. Let M n be the collection of n×n complex matrices equipped with operator norm. Suppose U, V ∈ M n are two unitary matrices, each possessing a gap larger than ∆ in their spectrum, which satisfy UV −V U ≤ . Then it is shown that there are two unitary operators X and Y satisfying XY − Y X = 0, where E(x) is a function growing slower than x 1 k for any positive integer k.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Note that we then obtain a stronger form of Osborne's result in [11] only requiring one matrix to have a spectral gap. We only need to transform one unitary into a Hermitian matrix, but we use a modification of a fractional linear transformation instead.…”
Section: Almost Commuting Hermitian and Normal Matricesmentioning
confidence: 71%
See 3 more Smart Citations
“…Note that we then obtain a stronger form of Osborne's result in [11] only requiring one matrix to have a spectral gap. We only need to transform one unitary into a Hermitian matrix, but we use a modification of a fractional linear transformation instead.…”
Section: Almost Commuting Hermitian and Normal Matricesmentioning
confidence: 71%
“…The geometry of a square, which is Some other examples (which we will discuss below) are that of almost commuting Hermitian and unitary matrices (which is related to the geometry of a cylinder/anulus) and two almost commuting unitaries (the geometry of the torus). The latter does not always have nearby commuting matrices, but [11] showed that if both unitaries have a spectral gap then one obtains nearby commuting unitaries. The proof given there involves using a matrix logarithm to reduce the unitary matrices with a spectral gap into Hermitian matrices.…”
Section: Almost Commuting Hermitian and Normal Matricesmentioning
confidence: 99%
See 2 more Smart Citations
“…For unitary matrices the above is however known to be generally false [11]. This is due to a K-theoretic obstruction [12][13][14], though it is true if this obstruction vanishes [7,8,15], or under the assumption of a spectral gap [16]. Imposing a form of self-duality analogous to time-reversal symmetry the relevant K-theoretic obstruction reduces to the spin Chern number of a fermionic system [17], highlighting a link between the fields of topologically ordered quantum systems [18] and approximately commuting matrices.…”
Section: Introductionmentioning
confidence: 99%